Sulindac external gel emplastrum and application thereof

By designing a stable three-dimensional network structure formed by the self-assembly of sulindac small molecule hydrogel and a biocompatible small molecule alkaline matrix, and combining it with adhesives and other excipients to prepare a topical gel patch, the problems of low water solubility of sulindac and difficult delivery of traditional dosage forms have been solved, achieving efficient and safe transdermal drug delivery and local treatment.

CN121197115APending Publication Date: 2025-12-26CHANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511504135.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-21
Publication Date
2025-12-26

AI Technical Summary

Technical Problem

Sulindac has low water solubility, resulting in low bioavailability and easy irritation to the gastric mucosa after oral administration. Traditional dosage forms are difficult to achieve efficient and precise drug delivery to the inflamed area. Existing hydrogels have poor compatibility with sulindac, affecting its chemical stability.

Method used

A sulindac small molecule hydrogel was designed, which formed a stable three-dimensional network structure by self-assembly with a biocompatible small molecule alkaline matrix. Combined with excipients such as adhesives and transdermal enhancers, a topical gel patch was prepared to achieve transdermal drug delivery.

Benefits of technology

Significantly improves the solubility and transdermal absorption efficiency of sulindac, ensuring that the patch adheres closely to the skin and is not easily detached, improving patient comfort and compliance, and providing a safe, efficient, and convenient new formulation for local treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121197115A_ABST
    Figure CN121197115A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of medicine, and particularly discloses sulindac external gel emplastrum and application thereof.The sulindac and a functional matrix with hydrophilic amino functional groups are subjected to molecular self-assembly, the functional matrix and carboxyl of the sulindac are subjected to non-covalent interaction through hydrogen bonds, ionic bonds and the like, and the sulindac external gel emplastrum is obtained. The stable micromolecular hydrogel with the three-dimensional network structure is spontaneously formed. The hydrogel can be prepared into an external gel emplastrum through simple compounding, the three-dimensional network structure endows the gel emplastrum with appropriate viscosity and skin adhesiveness, and the gel emplastrum can be tightly attached to the skin after being smeared on painful parts (such as joints and muscles) and is not prone to falling off due to movement. The preparation process has the advantages of simplicity and convenience in operation, economy and high efficiency, complex equipment is not needed in the micromolecule self-assembly process, the gel emplastrum can be compounded only through simple mixing, industrial production is facilitated, and the preparation method has high clinical conversion value and application potential.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of medicine, and specifically discloses a sulindac external use gel plaster and application thereof. BACKGROUND

[0002] In the field of medicine, non-steroidal anti-inflammatory drugs have become a key drug category for treating various inflammatory diseases due to their significant anti-inflammatory, analgesic and antipyretic effects. Sulindac, as an important representative, can reduce prostaglandin synthesis by inhibiting cyclooxygenase activity, and has a clear therapeutic effect on chronic inflammatory diseases such as rheumatoid arthritis and osteoarthritis, as well as acute pain caused by soft tissue injury, and is widely used in clinical inflammation management.

[0003] However, the clinical application of sulindac has been limited for a long time due to its own physicochemical properties and the defects of traditional dosage forms. On the one hand, the solubility of sulindac in water is extremely low (equilibrium solubility is only 11.77 μg / mL at 37℃), resulting in low bioavailability after oral administration, and the drug is difficult to effectively reach the target site of inflammation; on the other hand, when the oral preparation is absorbed through the gastrointestinal tract, it is easy to stimulate the gastric mucosa, causing adverse reactions such as ulcer and bleeding, which can be alleviated by enteric coating or combined with proton pump inhibitors, but it cannot fundamentally solve the safety hazards brought by the administration route, and it is difficult to achieve efficient and precise drug delivery in local inflammatory areas such as joint cavity and muscle, which restricts the full play of its therapeutic effect.

[0004] To break through the above bottleneck, researchers have been committed to developing new drug delivery systems. Hydrogel has become a hot research direction in drug delivery due to its excellent viscoelasticity, high biological safety, good biocompatibility and biodegradability. Compared with traditional high molecular weight hydrogel, small molecule hydrogel has unique advantages: better biological safety, reducing drug risk from the source, the matrix of small molecule gel is mostly biocompatible small molecules, and some are naturally occurring components in the body (such as amino acids), which can be safely metabolized by the body, and has very low irritation to skin, mucosa and other tissues, which can effectively avoid adverse reactions such as local inflammation and allergy caused by high molecular weight hydrogel due to high molecular chain residues and degradation product accumulation.

[0005] In the research of sulindac delivery system, although there have been some explorations of hydrogel, the existing technology still has some shortcomings: sulindac is a strong hydrophobic drug, and the existing hydrogel (such as traditional high molecular weight hydrogel) has poor compatibility between the hydrophilic network and the drug, and cannot improve the solubility of the drug through its own structure, and needs to rely on chemical solubilizers such as Tween-80 and dimethyl sulfoxide to assist drug loading, but such solubilizers may affect the chemical stability of sulindac (such as causing oxidative degradation). SUMMARY

[0006] Based on the deficiencies pointed out in the background art, the present application is aimed at the physicochemical properties of sulindac and clinical needs, and innovatively designs a sulindac small molecule hydrogel: a biocompatible small molecule matrix is selected, and a stable three-dimensional network structure is formed by self-assembly of the small molecule matrix and sulindac. As a key intermediate of the preparation, the hydrogel not only can significantly improve the solubility of sulindac by using the specific interaction (hydrogen bond, ionic bond) between the small molecule matrix and the carboxyl group of sulindac, but also can realize efficient and stable supersaturation release of the drug by network structure regulation, thereby laying a foundation for subsequent preparation development.

[0007] In order to further expand the clinical administration route of sulindac and solve the problem of drug delivery at local inflammation sites, the sulindac small molecule hydrogel is used as an intermediate of the preparation, and a sulindac external gel patch preparation is prepared by compounding a binder, a transdermal enhancer, a humectant and other excipients. The patch preparation is aimed at directly delivering the drug to local inflammation areas such as joints and muscles through transdermal administration, improving the transdermal absorption efficiency of the drug by the synergistic effect of the transdermal enhancer and the hydrogel, realizing local high-concentration enrichment of the drug, optimizing the tackiness and peel strength of the patch preparation, ensuring that the patch closely adheres to the skin after being applied and is not easy to fall off, and improving the patient's comfort and compliance when the patch is removed without skin damage. The sulindac external gel patch preparation is expected to provide a safe, efficient and convenient new preparation option for local treatment of inflammatory diseases.

[0008] The sulindac small molecule hydrogel is formed by mixing sulindac and a biocompatible small molecule basic matrix in a specific ratio, and then self-assembling under the action of deionized water after oscillation.

[0009] The molar ratio of sulindac to the biocompatible small molecule basic matrix is 1:10 to 10:1, and the biocompatible small molecule basic matrix is meglumine, arginine or lysine.

[0010] The sulindac external gel patch preparation is prepared by compounding the sulindac small molecule hydrogel as the core active component, a binder, a transdermal enhancer, a humectant, a pH regulator, a cosolvent and deionized water to prepare a colloid, then coating the sulindac colloid on a non-woven fabric as a backing, and finally covering a release film to obtain the gel patch preparation.

[0011] The binder is selected from one or more of carbomer, polyvinylpyrrolidone and gelatin; the transdermal enhancer is azone; the humectant is glycerol; the pH regulator is triethanolamine; and the cosolvent is propylene glycol.

[0012] The preparation method of the sulindac external gel patch preparation is as follows: 3.5-4.2 g of sulindac-matrix hydrogel is taken, and an adhesive (7.2 g), a humectant (glycerol 22 g), a cosolvent (propylene glycol 6 g), a transdermal enhancer (azone 2 g), and a pH regulator (triethanolamine 0.6 g) are added, then deionized water is added to make up to 100 g, and stirring is carried out at 15-45 DEG C for 0.5 h, and then swelling is carried out for 3-5 h to form a translucent gel. The gel prepared above is uniformly coated on a non-woven fabric backing material, the thickness is controlled to be 0.3-0.5 mm, a poly-isolation film is covered, and curing is carried out at 25 DEG C for 30-50 h to obtain the sulindac external gel patch preparation. The isolation film is a polyethylene film or a polypropylene film.

[0013] The beneficial effects of the present application are as follows: The present application focuses on the optimization of sulindac and the innovation of drug delivery routes, and provides a key technical solution for expanding the clinical application of sulindac by designing a sulindac small molecule hydrogel. At the same time, the hydrogel as a core intermediate for the development of sulindac external gel patch preparation provides a new idea for the diversification of sulindac preparations.

[0014] The sulindac external gel patch preparation has good skin compatibility and use comfort. The crosslinking degree of the adhesive (carbomer, polyvinylpyrrolidone, and gelatin) is accurately controlled to achieve the best balance between the tackiness and peel strength of the patch preparation. After application, the patch can closely adhere to the skin and is not easy to fall off even in dynamic scenarios such as joint movement. When the patch is removed, there is no obvious pain, and the stratum corneum is not damaged, which can reduce the risk of skin irritation.

[0015] The sulindac external gel patch preparation has soft texture and good flexibility, and can be applied to irregular parts such as joints and muscles according to the skin contour without obvious foreign body sensation. The air permeability of the non-woven fabric backing can reduce the stuffy feeling of the applied part, significantly improving the comfort and compliance of long-term medication of patients. It is expected to provide a new preparation option for the treatment of inflammatory diseases, and has strong clinical transformation value and application potential. BRIEF DESCRIPTION OF DRAWINGS

[0016] Figure 1 (A) sample images and (B) SEM images of sulindac-meglumine hydrogel prepared in Example 1 (a), sulindac-arginine hydrogel prepared in Example 6 (b), and sulindac-lysine hydrogel prepared in Example 11 (c).

[0017] Figure 2 Rheological test chart of sulindac-meglumine hydrogel prepared in Example 1 (a: strain sweep, b: frequency sweep).

[0018] Figure 3 Rheological test chart of sulindac-arginine hydrogel prepared in Example 6 (a: strain sweep, b: frequency sweep).

[0019] Figure 4 The rheological test diagrams of the sulindac-lysine hydrogel prepared in Example 11 are as follows: (a: strain scan, b: frequency scan).

[0020] Figure 5 This is a powder X-ray diffraction pattern of the dry gel prepared from the sulindac-glucamine hydrogel in Example 1.

[0021] Figure 6 This is a powder X-ray diffraction pattern of the dry gel prepared from the sulinic acid-arginine hydrogel in Example 6.

[0022] Figure 7 This is a powder X-ray diffraction pattern of the dry gel prepared from the sulinic acid-lysine hydrogel in Example 11.

[0023] Figure 8 This is the infrared spectrum of the sulindac-glucamine dry gel prepared in Example 1.

[0024] Figure 9 This is the infrared spectrum of the sulindac-arginine dry gel prepared in Example 6.

[0025] Figure 10 This is the infrared spectrum of the sulindac-lysine dry gel prepared in Example 11.

[0026] Figure 11 The cumulative release curves are those of the sulindac-glucamine hydrogel (A) prepared in Example 1, the sulindac-arginine hydrogel (B) prepared in Example 6, and the sulindac-lysine hydrogel (C) prepared in Example 11.

[0027] Figure 12 The non-leakage release curves are those of the sulindac-glucamine hydrogel (A) prepared in Example 1, the sulindac-arginine hydrogel (B) prepared in Example 6, and the sulindac-lysine hydrogel (C) prepared in Example 11.

[0028] Figure 13 These are images of the topical plasters prepared in Example 1 (A), Example 6 (B), and Example 11 (C) of sulindac-glucamine hydrogel. Detailed Implementation

[0029] The present invention will be further described below with reference to specific embodiments.

[0030] Example 1: Weigh 4g of sulindac and meglumine in equal molar ratio, place them in a 10mL glass bottle, mix them at 25℃ using a suspension mixer, add 0.45mL of deionized water, and shake for 10min to obtain sulindac-meglumine hydrogel.

[0031] Take 4g of the sulindac-meglumine hydrogel, add adhesive (carbomer 3.2g, polyvinylpyrrolidone 2.5g, gelatin 1.5g), humectant (glycerol 22g), cosolvent (propylene glycol 6g), penetration enhancer (azone 2g), pH adjuster (triethanolamine 0.6g), then add deionized water to make up to 100g, stir at 25°C for 0.5h, then swell for 4h to form a translucent gel. The gel prepared above is uniformly coated on the non-woven backing material, the thickness is controlled to be 0.4mm, covered with a polyethylene release film, and cured at 25°C for 40h to obtain a sulindac topical gel patch.

[0032] Example 2: Take 4g of sulindac and meglumine in equal molar ratio, place them in a 10mL glass bottle, mix them uniformly at 25°C with a suspension instrument, add 0.45mL of deionized water, and shake for 10min to obtain a sulindac-meglumine hydrogel.

[0033] Take 4g of the sulindac-meglumine hydrogel, add adhesive (carbomer 3.2g, polyvinylpyrrolidone 2.5g, gelatin 1.5g), humectant (glycerol 22g), cosolvent (propylene glycol 6g), penetration enhancer (azone 2g), pH adjuster (triethanolamine 0.6g), then add deionized water to make up to 100g, stir at 15°C for 0.5h, then swell for 4h to form a translucent gel. The gel prepared above is uniformly coated on the non-woven backing material, the thickness is controlled to be 0.4mm, covered with a polyethylene release film, and cured at 15°C for 40h to obtain a sulindac topical gel patch.

[0034] Example 3: Take 4g of sulindac and meglumine in equal molar ratio, place them in a 10mL glass bottle, mix them uniformly at 40°C with a suspension instrument, add 0.45mL of deionized water, and shake for 10min to obtain a sulindac-meglumine hydrogel.

[0035] Take 4g of the sulindac-meglumine hydrogel, add adhesive (carbomer 3.2g, polyvinylpyrrolidone 2.5g, gelatin 1.5g), humectant (glycerol 22g), cosolvent (propylene glycol 6g), penetration enhancer (azone 2g), pH adjuster (triethanolamine 0.6g), then add deionized water to make up to 100g, stir at 45°C for 0.5h, then swell for 4h to form a translucent gel. The gel prepared above is uniformly coated on the non-woven backing material, the thickness is controlled to be 0.4mm, covered with a polyethylene release film, and cured at 45°C for 40h to obtain a sulindac topical gel patch.

[0036] Example 4: Take 4g of sulindac and meglumine in equal molar ratio, place them in a 10ml glass bottle, mix them evenly at 25°C with a suspension instrument, add 0.45ml of deionized water, and shake for 10 minutes to obtain a sulindac-meglumine hydrogel.

[0037] Take 4g of sulindac-meglumine hydrogel, add adhesive (carbomer 3.2g, gelatin 4g), humectant (glycerol 22g), cosolvent (propylene glycol 6g), penetration enhancer (azone 2g), pH adjuster (triethanolamine 0.6g), then add deionized water to make up to 100g, stir at 25°C for 0.5h, then swell for 4h to form a translucent gel. The gel prepared above is evenly coated on a non-woven backing material, the thickness is controlled to be 0.4mm, covered with a polyethylene release film, and cured at 25°C for 40h to obtain a sulindac topical gel patch.

[0038] Example 5: Take 4g of sulindac and meglumine in equal molar ratio, place them in a 10ml glass bottle, mix them evenly at 25°C with a suspension instrument, add 0.45ml of deionized water, and shake for 10 minutes to obtain a sulindac-meglumine hydrogel.

[0039] Take 4g of sulindac-meglumine hydrogel, add adhesive (carbomer 3.2g, polyvinylpyrrolidone 4g), humectant (glycerol 22g), cosolvent (propylene glycol 6g), penetration enhancer (azone 2g), pH adjuster (triethanolamine 0.6g), then add deionized water to make up to 100g, stir at 25°C for 0.5h, then swell for 4h to form a translucent gel. The gel prepared above is evenly coated on a non-woven backing material, the thickness is controlled to be 0.4mm, covered with a polyethylene release film, and cured at 25°C for 40h to obtain a sulindac topical gel patch.

[0040] Example 6: Take 4g of sulindac and arginine in equal molar ratio, place them in a 10ml glass bottle, mix them evenly at 25°C with a suspension instrument, add 0.45ml of deionized water, and shake for 10 minutes to obtain a sulindac-arginine hydrogel.

[0041] Take 4g of sulindac-arginine hydrogel, add adhesive (carbomer 3.2g, polyvinylpyrrolidone 2.5g, gelatin 1.5g), humectant (glycerol 22g), cosolvent (propylene glycol 6g), penetration enhancer (azone 2g), pH adjuster (triethanolamine 0.6g), then add deionized water to make up to 100g, stir at 25°C for 0.5h, then swell for 4h to form a translucent gel. The gel prepared above is evenly coated on a non-woven backing material, the thickness is controlled to be 0.4mm, covered with a polyethylene release film, and cured at 25°C for 40h to obtain a sulindac topical gel patch.

[0042] Example 7: Take 4g of sulindac and arginine in equal molar ratio, place them in a 10ml glass bottle, mix them evenly at 25°C with a suspension instrument, add 0.45ml of deionized water, and shake for 10 minutes to obtain a sulindac-arginine hydrogel.

[0043] Take 4g of sulindac-arginine hydrogel, add adhesive (carbomer 3.2g, polyvinylpyrrolidone 2.5g, gelatin 1.5g), humectant (glycerol 22g), cosolvent (propylene glycol 6g), transdermal enhancer (azone 2g), pH adjuster (triethanolamine 0.6g), and then add deionized water to make up to 100g. Stir for 0.5h at 15°C, then swell for 4h to form a translucent gel. The prepared gel is evenly coated on a non-woven backing material, the thickness is controlled to be 0.4mm, a polyethylene release film is covered, and it is cured at 15°C for 40h to obtain a sulindac topical gel patch.

[0044] Example 8: Take 4g of sulindac and arginine in equal molar ratio, place them in a 10ml glass bottle, mix them evenly at 25°C with a suspension instrument, add 0.45ml of deionized water, and shake for 10 minutes to obtain a sulindac-arginine hydrogel.

[0045] Take 4g of sulindac-arginine hydrogel, add adhesive (carbomer 3.2g, polyvinylpyrrolidone 2.5g, gelatin 1.5g), humectant (glycerol 22g), cosolvent (propylene glycol 6g), transdermal enhancer (azone 2g), pH adjuster (triethanolamine 0.6g), and then add deionized water to make up to 100g. Stir for 0.5h at 45°C, then swell for 4h to form a translucent gel. The prepared gel is evenly coated on a non-woven backing material, the thickness is controlled to be 0.4mm, a polyethylene release film is covered, and it is cured at 45°C for 40h to obtain a sulindac topical gel patch.

[0046] Example 9: Take 4g of sulindac and arginine in equal molar ratio, place them in a 10ml glass bottle, mix them evenly at 25°C with a suspension instrument, add 0.45ml of deionized water, and shake for 10 minutes to obtain a sulindac-arginine hydrogel.

[0047] Take 4g of sulindac-arginine hydrogel, add adhesive (carbomer 3.2g, gelatin 4g), humectant (glycerol 22g), cosolvent (propylene glycol 6g), transdermal enhancer (azone 2g), pH adjuster (triethanolamine 0.6g), and then add deionized water to make up to 100g. Stir for 0.5h at 25°C, then swell for 4h to form a translucent gel. The prepared gel is evenly coated on a non-woven backing material, the thickness is controlled to be 0.4mm, a polyethylene release film is covered, and it is cured at 25°C for 40h to obtain a sulindac topical gel patch.

[0048] Example 10: Take 4g of sulindac and arginine in equal molar ratio, place in a 10ml glass bottle, mix at 25°C with suspension instrument, add 0.45ml of deionized water, shake for 10min, and then sulindac-arginine hydrogel is obtained.

[0049] Take 4g of sulindac-arginine hydrogel, add adhesive (carbomer 3.2g, polyvinylpyrrolidone 4g), humectant (glycerol 22g), cosolvent (propylene glycol 6g), transdermal enhancer (azone 2g), pH adjuster (triethanolamine 0.6g), and then add deionized water to make up to 100g. After stirring at 25°C for 0.5h, swell for 4h to form a translucent gel. The prepared gel is uniformly coated on the non-woven backing material, the thickness is controlled to be 0.4mm, covered with a polyethylene release film, and then cured at 25°C for 40h to obtain a sulindac topical gel patch.

[0050] Example 11: Take 4g of sulindac and lysine in equal molar ratio, place in a 10ml glass bottle, mix at 25°C with suspension instrument, add 0.45ml of deionized water, shake for 10min, and then sulindac-lysine hydrogel is obtained.

[0051] Take 4g of sulindac-lysine hydrogel, add adhesive (carbomer 3.2g, polyvinylpyrrolidone 2.5g, gelatin 1.5g), humectant (glycerol 22g), cosolvent (propylene glycol 6g), transdermal enhancer (azone 2g), pH adjuster (triethanolamine 0.6g), and then add deionized water to make up to 100g. After stirring at 25°C for 0.5h, swell for 4h to form a translucent gel. The prepared gel is uniformly coated on the non-woven backing material, the thickness is controlled to be 0.4mm, covered with a polyethylene release film, and then cured at 25°C for 40h to obtain a sulindac topical gel patch.

[0052] Example 12: Take 4g of sulindac and lysine in equal molar ratio, place in a 10ml glass bottle, mix at 25°C with suspension instrument, add 0.45ml of deionized water, shake for 10min, and then sulindac-lysine hydrogel is obtained.

[0053] Take 4g of sulindac-lysine hydrogel, add adhesive (carbomer 3.2g, polyvinylpyrrolidone 2.5g, gelatin 1.5g), humectant (glycerol 22g), cosolvent (propylene glycol 6g), transdermal enhancer (azone 2g), pH adjuster (triethanolamine 0.6g), and then add deionized water to make up to 100g. After stirring at 25°C for 0.5h, swell for 4h to form a translucent gel. The prepared gel is uniformly coated on the non-woven backing material, the thickness is controlled to be 0.4mm, covered with a polyethylene release film, and then cured at 25°C for 40h to obtain a sulindac topical gel patch.

[0054] Example 13: Take 4g of sulindac and lysine in equal molar ratio, place them in a 10ml glass bottle, mix them evenly at 25°C with a suspension instrument, add 0.45ml of deionized water, and shake for 10 minutes to obtain a sulindac-lysine hydrogel.

[0055] Take 4g of sulindac-lysine hydrogel, add adhesive (carbomer 3.2g, polyvinylpyrrolidone 2.5g, gelatin 1.5g), humectant (glycerol 22g), cosolvent (propylene glycol 6g), transdermal enhancer (azone 2g), pH adjuster (triethanolamine 0.6g), and then add deionized water to make up to 100g. Stir for 0.5h at 45°C, then swell for 4h to form a translucent gel. The gel prepared above is evenly coated on a non-woven backing material, the thickness is controlled to be 0.4mm, a polyethylene release film is covered, and it is cured at 45°C for 40h to obtain a sulindac topical gel patch.

[0056] Example 14: Take 4g of sulindac and lysine in equal molar ratio, place them in a 10ml glass bottle, mix them evenly at 25°C with a suspension instrument, add 0.45ml of deionized water, and shake for 10 minutes to obtain a sulindac-lysine hydrogel.

[0057] Take 4g of sulindac-lysine hydrogel, add adhesive (carbomer 3.2g, gelatin 4g), humectant (glycerol 22g), cosolvent (propylene glycol 6g), transdermal enhancer (azone 2g), pH adjuster (triethanolamine 0.6g), and then add deionized water to make up to 100g. Stir for 0.5h at 25°C, then swell for 4h to form a translucent gel. The gel prepared above is evenly coated on a non-woven backing material, the thickness is controlled to be 0.4mm, a polyethylene release film is covered, and it is cured at 25°C for 40h to obtain a sulindac topical gel patch.

[0058] Example 15: Take 4g of sulindac and lysine in equal molar ratio, place them in a 10ml glass bottle, mix them evenly at 25°C with a suspension instrument, add 0.45ml of deionized water, and shake for 10 minutes to obtain a sulindac-lysine hydrogel.

[0059] Take 4g of sulindac-lysine hydrogel, add adhesive (carbomer 3.2g, polyvinylpyrrolidone 4g), humectant (glycerol 22g), cosolvent (propylene glycol 6g), transdermal enhancer (azone 2g), pH adjuster (triethanolamine 0.6g), and then add deionized water to make up to 100g. Stir for 0.5h at 25°C, then swell for 4h to form a translucent gel. The gel prepared above is evenly coated on a non-woven backing material, the thickness is controlled to be 0.4mm, a polyethylene release film is covered, and it is cured at 25°C for 40h to obtain a sulindac topical gel patch.

[0060] Comparative Example 1: 4 g of sulindac and levo- mifepristone were weighed in a 10 mL glass bottle, mixed at 25 °C using a suspension instrument, 0.45 mL of deionized water was added, and oscillation was performed for 10 min. The state of the drug in the bottle was observed.

[0061] 4 g of sulindac-levo-mifepristone hydrogel was taken, and a binding agent (3.2 g of carbomer, 2.5 g of polyvinylpyrrolidone, and 1.5 g of gelatin), a humectant (22 g of glycerol), a cosolvent (6 g of propylene glycol), a transdermal enhancer (2 g of azone), and a pH regulator (0.6 g of triethanolamine) were added. Deionized water was added to make up to 100 g. After stirring at 25 °C for 0.5 h, swelling was performed for 4 h to form a semi-transparent gel. The gel prepared above was uniformly coated on a non-woven backing material, the thickness was controlled to be 0.4 mm, a polyethylene release film was covered, and curing was performed at 25 °C for 40 h to obtain a sulindac external use gel patch.

[0062] Comparative Example 2: 4 g of sulindac and ergotamine were weighed in a 10 mL glass bottle, mixed at 25 °C using a suspension instrument, 0.45 mL of deionized water was added, and oscillation was performed for 10 min. The state of the drug in the bottle was observed.

[0063] 4 g of sulindac-ergotamine hydrogel was taken, and a binding agent (3.2 g of carbomer, 2.5 g of polyvinylpyrrolidone, and 1.5 g of gelatin), a humectant (22 g of glycerol), a cosolvent (6 g of propylene glycol), a transdermal enhancer (2 g of azone), and a pH regulator (0.6 g of triethanolamine) were added. Deionized water was added to make up to 100 g. After stirring at 25 °C for 0.5 h, swelling was performed for 4 h to form a semi-transparent gel. The gel prepared above was uniformly coated on a non-woven backing material, the thickness was controlled to be 0.4 mm, a polyethylene release film was covered, and curing was performed at 25 °C for 40 h to obtain a sulindac external use gel patch.

[0064] Test Example 1: The sulindac-matrix three kinds of bioaffinity hydrogels prepared in Examples 1, 6, and 11 were detected, and the details are as follows: The scanning electron microscope analysis was performed using a TM4000 table type scanning electron microscope (HITACHI, Japan), and the probe current was set to 20 μA, the acceleration voltage was set to 15 kV, and the counting time was set to 60 s during the test process.

[0065] The determination results: the rheological test results of the sulindac-meglumine, sulindac-arginine, and sulindac-lysine hydrogels in Examples 1, 6, and 11 are shown in Table 1. Figure 1 B. The scanning electron microscope observation results show that the three kinds of sulindac-matrix hydrogels all present irregular folded and stacked porous three-dimensional network structures.

[0066] 2. Rheological test A Kinexus pro rotational rheometer (Malvern, the Great Britain) was used with a temperature control of 25℃, a gap of 1 mm, and a parallel plate diameter of 20 mm. The frequency was 1 Hz with a strain range of 0.1%~1000% during the strain sweep. The fixed strain was 3% with a frequency range of 0.1~100 rad·s during the frequency sweep. -1 .

[0067] Results: The viscoelastic properties of the sulfasalazine hydrogels were characterized by dynamic oscillatory rheological experiments. The rheological test results of the sulfasalazine-meglumine hydrogel prepared in Example 1 are shown in Figure 2 . The experimental results show that the storage modulus (G') and the loss modulus (G'') of the sulfasalazine-meglumine hydrogel remain stable when the strain amplitude is less than 3%, indicating that the network structure is in the linear viscoelastic region. When the strain exceeds the threshold of 3%, the modulus value decreases sharply and the viscoelastic response is reversed (G''>G'), which means that the three-dimensional network structure is destroyed. Similarly, the upper limit of the linear viscoelastic region of the sulfasalazine-arginine hydrogel prepared in Example 6 ( Figure 3 ) and the sulfasalazine-lysine hydrogel prepared in Example 11 ( Figure 4 ) is 10% and 5% strain, respectively. Once the critical value is exceeded, the modulus relationship is reversed and the system exhibits fluid-like characteristics. The viscoelasticity study confirms that all three hydrogels have the response characteristics of typical viscoelastic materials.

[0068] The viscoelastic response of the sulfasalazine hydrogel was characterized by angular frequency sweep test (0.1~100 rad / s, strain 3%, within the linear viscoelastic region). The results show that the G' and G'' of the sulfasalazine-meglumine hydrogel increase synchronously with the increase of frequency; the G' of the sulfasalazine-arginine hydrogel is always higher than the G'' within the entire frequency range, and it is less sensitive to frequency changes, which reflects the mechanical strength that meets the standard of hydrogel; the dynamic frequency scanning results of the sulfasalazine-lysine hydrogel are similar to those of the sulfasalazine-meglumine hydrogel, and both G' and G'' gradually increase with the increase of the applied frequency. In summary, all three hydrogels exhibit an elastic-dominated property (G'>G'').

[0069] 3. Powder X-ray diffraction A SmartLab (9) X-ray diffractometer (Rigaku, Japan) was used with the following test parameters: Cu-Ka radiation as the target source (wavelength 1.5406 Å), tube voltage 40 kV, tube current 40 mA; scanning range 2θ, 3-50°, step size 0.02°, scanning speed 4° / min.

[0070] Results: The change in crystallinity of the sulfasalazine gel before and after gel formation was characterized by X-ray powder diffraction (results shown in Figures 5-7The lack of crystallinity in a substance can be determined by the presence of amorphous diffraction rings in X-ray powder diffraction (XRPD) patterns. Experimental results show that crystalline sulinic acid exhibits crystal diffraction peaks at 2θ values ​​of 9.48°, 12.14°, 13.86°, 15.04°, 17.78°, 18.38°, 21.34°, 22.51°, 24.02°, 24.75°, 26.28°, and 28.44°; while crystalline meglumine, arginine, and lysine show peaks at 2θ values ​​of 10°, 10°, and 10°, respectively. o ~30°, 11 o ~36°, 10 o Multiple characteristic diffraction peaks are observed within the range of ~35°.

[0071] The diffraction patterns of the physical mixtures of sulindac-meglumine, sulindac-arginine, and sulindac-lysine are all superpositions of the characteristic peaks of the corresponding crystalline components of the two active pharmaceutical ingredients. In contrast, the X-ray powder diffraction patterns of the sulindac-meglumine gel, sulindac-arginine gel, and sulindac-lysine gel show a significant decrease in crystalline diffraction peaks, indicating that these three gels are closer to an amorphous state overall.

[0072] 4. Fourier transform infrared spectroscopy A Nicolet iS50 instrument (Thermo, American) was used, with the following settings: resolution 4cm. -1 Scanning range 4000~500cm -1 A total of 64 scans were performed.

[0073] Measurement results: by Figure 8 It can be seen that the characteristic peak wavenumber (cm²) of the infrared spectrum of the sulindac-meglumine hydrogel sample in Example 1 is... -1 The values ​​are: 3400.85, 2934.64, 2916.32, 2360.92, 2301.14, 1603.52, 1606.61, 1464.67, 1432.85, 1373.06, 1294.48, 1167.20, 1090.60, 1055.83, 973.87, 910.23, 865.39, 845.63, 798.38, 657.12, 533.70, 503.32.

[0074] like Figure 9 It can be seen that the characteristic peak wavenumber (cm²) of the infrared spectrum of the sulindac-arginine hydrogel sample in Example 6 is... -1) are: 3389.95, 2359.96, 1617.01, 1477.68, 1466.59, 1425.13, 1363.42, 1287.25, 1273.75, 1202.39, 1164.79, 1133.45, 1085.24, 1033.65, 985.44, 965.19, 893.36, 809.47, 716.42, 598.30, 535.14.

[0075] As Figure 10 It can be seen that the infrared spectrum characteristic peak wave number (cm -1 ) of the sample of the sulindac-lysine hydrogel in Example 11 is: 3433.47, 2858.95, 2350.31, 1599.66, 1468.04, 1424.65, 1369.21, 1264.11, 1191.79, 1166.24, 1091.03, 1033.17, 964.23, 917.95, 862.98, 809.95, 731.85, 699.06, 649.41, 598.78, 580.46, 537.07.

[0076] Test Example 2: Solubility determination of a physical mixture of sulindac and a matrix, the sulindac-meglumine hydrogel prepared in Examples 1, 6, 11, the sulindac-arginine hydrogel, and the sulindac-lysine hydrogel was carried out as follows: The physical mixture of sulindac and a matrix was weighed by a molar ratio of 1:1 of the drug and the matrix powder, placed in a 10 mL glass bottle, and the two powders were uniformly mixed by a vortex shaker to obtain the physical mixture of sulindac-matrix.

[0077] An excess of sulindac crystals, a physical mixture of sulindac-matrix, and a sulindac-matrix hydrogel composition were weighed and placed in 10 mL centrifuge tubes in triplicate, 5 mL of deionized water was added, and the mixture was placed in a constant temperature shaker and shaken for 24 h (200 rpm, 37°C). 2 mL of supernatant was taken, filtered with a 0.22 μm water phase microporous filter, and determined by high performance liquid chromatography (HPLC) to calculate the solubility of the drug in deionized water.

[0078] The high performance liquid chromatography conditions are as follows: The detection was carried out by using an Agilent-1260 type high performance liquid chromatograph, an Ultimate XB-C18 chromatographic column with a size of 4.6 mm x 250 mm and a filler particle size of 5 μm was selected, the mobile phase was a mixture of acetonitrile and water containing 0.3% phosphoric acid in a volume ratio of 50:50, the elution flow rate of the chromatographic column was set to 1.0 mL / min, and the detection wavelength of the target component was selected as 320 nm.

[0079] The results of the determination: the solubility of the sulindac-meglumine hydrogel, the sulindac-arginine hydrogel and the sulindac-lysine hydrogel in deionized water in Examples 1, 6 and 11 are shown in Table 1.

[0080] Table 1 Water solubility of sulindac crystal, sulindac-matrix physical mixture and sulindac hydrogel

[0081] As can be seen from Table 1, the equilibrium solubility of the crystal SUL in water at 37℃ is only 11.77 μg / mL. The solubility of the sulindac-meglumine hydrogel (6432.13 μg / mL), the sulindac-arginine hydrogel (5971.17 μg / mL) and the sulindac-lysine hydrogel (6228.22 μg / mL) in Examples is found to be significantly improved by 546.48 times, 502.73 times and 529.16 times, respectively, compared with the crystal sulindac. p <0.01).

[0082] Test Example 3: The sulindac-meglumine hydrogel, the sulindac-arginine hydrogel and the sulindac-lysine hydrogel prepared in Examples 1, 6 and 11 were subjected to release test under sink condition, as follows: Sulindac crystal, sulindac-meglumine crystal physical mixture, sulindac-arginine physical mixture, sulindac-lysine physical mixture, sulindac-meglumine hydrogel, sulindac-arginine hydrogel and sulindac-lysine hydrogel in Examples were weighed, in triplicate. According to the second method of General Rules 0931 in Chinese Pharmacopoeia 2020 edition, the release test under sink condition was carried out by slurry method. The release medium was deionized water, the medium temperature was 37℃, the medium volume was 900 mL, and the rotation speed was 100 rpm. 2 mL was taken at 2, 5, 10, 15, 20, 30, 45, 60, 90 and 120 min, and 2 mL of isothermal and equal volume of dissolution medium was supplemented at the same time. The liquid was passed through a 0.22 μm water phase microporous filter membrane, and 10 μL of the filtrate was taken for HPLC analysis.

[0083] The results of the determination: the cumulative release rate curves of the sulindac-meglumine hydrogel, the sulindac-arginine hydrogel and the sulindac-lysine hydrogel under sink condition in Examples 1, 6 and 11 are shown in Figure 11The cumulative release of sulindac-arginine hydrogel was 75.21% within 20 min, which was significantly better than that of sulindac crystals (9.82%), and the release amount increased to 81.41% at 120 min, which was significantly better than that of sulindac crystals (35.75%). Sulindac lysine hydrogel released 78.68% of sulindac at 20 min, while the cumulative release amount of sulindac crystals was 9.82%. The cumulative release amount of sulindac-lysine increased to 79.25% at 120 min, which was much higher than that of sulindac crystals (35.75%). The experiment proved that the three kinds of sulindac hydrogel systems could significantly accelerate the release of drugs under sink conditions.

[0084] Test Example 4: Sulindac-matrix three kinds of small molecule hydrogels of Example 1, 6, 11 were tested for release under non-sink conditions, as follows: A certain amount of sulindac crystals, physical mixture of sulindac and meglumine crystals, physical mixture of sulindac and arginine crystals, physical mixture of sulindac and lysine crystals, sulindac-matrix three kinds of small molecule hydrogels in the examples were weighed, in triplicate. According to the second method of Chinese Pharmacopoeia 2020 edition four general rules 0931, the slurry method was used for non-sink release evaluation. The release medium was deionized water, the medium temperature was 37℃, the medium volume was 200mL, and the rotation speed was 100rpm. 2mL was taken at 5, 10, 20, 30, 45, 60, 90, 120, 240, 360, 480 and 720min, and the same volume of dissolution medium was supplemented at the same time. The liquid was passed through a 0.22μm water phase microporous filter membrane, and 10μL of the filtrate was taken for HPLC analysis.

[0085] The determination results: the non-sink release curve comparison chart of sulindac hydrogel is shown in Figure 12 Figure 12 ​It can be seen that under the condition of no pinhole, the release concentration of sulindac crystal is only 16.30 μg / mL at 120 min, while the concentration of sulindac-meglumine hydrogel has increased to 273.34 μg / mL. With the extension of time, all samples gradually approach their saturated concentrations. After 720 min, the concentration of sulindac-meglumine hydrogel reaches 276.17 μg / mL, which is 14.95 times higher than that of sulindac crystal (18.28 μg / mL). For the sulindac-arginine system, the hydrogel continuously maintains a stable supersaturated state within 12 h without concentration attenuation, and the concentration reaches 277.08 μg / mL at 720 min, which is 22.56 times that of sulindac crystal (18.28 μg / mL). For the sulindac-lysine hydrogel, the sulindac concentration reaches 269.12 μg / mL at 720 min, which is 14.72 times that of sulindac crystal (18.28 μg / mL).

[0086] Test Example 5: The gel-type external use patch preparations prepared in Example 1, Example 6, and Example 11 were subjected to performance testing, and the test results are as follows. Figure 13 A is the external use patch preparation of sulindac-meglumine hydrogel prepared in Example 1, Figure 13 B is the external use patch preparation of sulindac-arginine hydrogel prepared in Example 6, Figure 13 C is the external use patch preparation of sulindac-lysine hydrogel prepared in Example 11. According to the four-part patch preparation inspection method of the Chinese Pharmacopoeia 2020 edition, the appearance, adhesion, and peel strength of the patch preparation were scored, and the sum of the scores was the comprehensive score. The test method and scoring standard are shown in Table 2.

[0087] Table 2: Forming process investigation indicators, methods, and scoring standards for sulindac hydrogel external use patch preparations

[0088] Table 3: Preparation verification test results of sulindac hydrogel external use patch preparations

[0089] The sulindac-meglumine, sulindac-arginine, and sulindac-lysine hydrogel external use patch preparations were comprehensively investigated in terms of appearance, initial adhesion, adhesion retention, and peel strength, and the total scores were 86.80, 85.15, and 84.08, respectively, all of which met the pharmacopoeia standards (Table 3) and were significantly better than the sulindac-voacoline and sulindac-ergometrine comparative systems. The forming process achieved a balance of preparation performance through precise control of the ratio of excipients and solidification parameters, and had potential for industrial production, which could provide a reliable dosage form selection for the local treatment of inflammatory diseases.

Claims

1. A topical gel patch for sulindac, characterized in that, The sulindac topical gel patch is prepared by using non-woven fabric as a backing, coating it with sulindac colloid, and then covering it with a release film; the sulindac colloid is prepared by sulindac small molecule hydrogel, adhesive, transdermal activator, moisturizer, pH adjuster, solubilizer and deionized water.

2. The sulindac topical gel patch according to claim 1, characterized in that, Sulinic acid small molecule hydrogels are formed by the self-assembly of sulinic acid and a biocompatible small molecule alkaline matrix in the presence of deionized water.

3. The sulindac topical gel patch according to claim 2, characterized in that, The molar ratio of sulindac to the biocompatible small molecule basic matrix is ​​1:10 to 10:1, and the biocompatible small molecule basic matrix is ​​meglumine, arginine, and lysine.

4. The sulindac topical gel patch according to claim 1, characterized in that, The adhesive is selected from one or more of carbomer, polyvinylpyrrolidone, and gelatin; the transdermal penetration enhancer is azone, the humectant is glycerin, the pH adjuster is triethanolamine, and the cosolvent is propylene glycol.

5. The topical gel patch of sulindac according to claim 1, characterized in that, The composition of sulindac colloid by mass percentage is as follows: 3.5%~4.2% sulindac small molecule hydrogel, 7.2% binder, 2% transdermal penetration enhancer, 22% moisturizer, 6% cosolvent, 0.6% pH adjuster, and the balance is deionized water.

6. The sulindac topical gel patch according to claim 1, characterized in that, The preparation method of the gel patch is as follows: take sulindac small molecule hydrogel, add adhesive, moisturizer, solubilizer, transdermal penetration promoter and pH adjuster, then add deionized water, stir to swell and let stand to form a semi-transparent colloid; then evenly coat the colloid on the non-woven fabric backing, cover with a release film, let stand to cure, and you will get sulindac external gel patch.

7. The sulindac topical gel patch according to claim 6, characterized in that, The temperature for preparing the colloid by stirring is 15~45℃, and the swelling time by stirring is 3~5h.

8. The sulindac topical gel patch according to claim 6, characterized in that, The backing thickness is 0.3~0.5mm; the release liner is a polyethylene film or a polypropylene film, and the curing time is 30~50h.

9. An application of the sulindac topical gel patch according to claim 1, characterized in that, The plaster is used to prepare a plaster for treating arthritis and inflammatory diseases caused by soft tissue injuries.